Julgamento perceptivo-auditivo das oclusivas velares associadas à fissura labiopalatina por juízes com e sem experiência - Marino, Viviane Cristina De Castro; Borges, Tayrine Sousa Marques; Jurado, Mayalle Rocha Bonfim; Canales, Mariana Rodrigues; Lima-gregio, Aveliny Mantovan; Dutka, Jeniffer De Cássia Rillo (ABRAMO Associação Brasileira de Motricidade Orofacial, 2015)
ABSTRACT:Purpose: to verify: a) the level of agreement among judges during auditory-perceptual assessment of velar plosive sounds before and after speech therapy, b) the possible influence of the phonetic composition from the speech samples in this correlation c) whether the assessments from judges with experience differ from those without experience in given conditions.Methods: 60 speech samples of children with cleft lip and palate, 30 before and 30 after speech therapy, and 30 samples from children without cleft lip and palate and with normal speech were rated by a group of 9 judges. Three speech-language pathologists established the gold standard consensual judgments for the study. Six other judges assessed the samples for this study: three considered experienced ones (speech-language pathologists) and three non-experienced (undergraduate students). The speech samples included velar consonants /k/ and /g/ and vowels /a/, /i/ and /u/. Judges were instructed to assess the presence or absence of velar consonants or presence of CA.Results: Kappa statistics revealed moderate agreement among experienced judges and low agreement among the judges without experience for samples recorded before speech therapy. Phonetic context had an effect on the assessments before and after speech therapy. Assessments were significantly better among experienced judges before speech therapy (p-valor <0,001).Conclusion: experience of judges and phonetic composition from the speech samples influence perceptual judgments of CA.

RESUMO:Objetivo: verificar: a) o grau de concordância de juízes no julgamento perceptivo-auditivo da produção de oclusivas velares, antes e depois da fonoterapia; b) a possível influência da composição fonética das amostras de fala nesta concordância e c) se os julgamentos obtidos por juízes com experiência diferem daqueles obtidos por juízes sem experiência, nas condições investigadas.Métodos: 60 amostras de fala de uma criança com fissura labiopalatina (30 previamente e 30 posteriormente a fonoterapia) e 30 amostras de fala de uma criança com fala típica (normal) foram julgadas por um grupo de 9 juízes. Três fonoaudiólogos estabeleceram os julgamentos consensuais padrão ouro para o estudo. Seis outros juízes julgaram as amostras: três considerados com experiência (fonoaudiólogos) e três sem experiência (alunos de graduação). As amostras de fala incluíram palavras constituídas pelas oclusivas velares /k/ e /g/ combinada com as vogais /a/, /i/ e /u/. Os juízes foram instruídos a julgar a presença, a ausência das oclusivas velares ou a presença de AC nestas amostras.Resultados: verificou-se diferenças no grau de concordância de juízes com experiência (Kappa moderada) e sem experiência (Kappa baixo) para os julgamentos realizados na condição pré-fonoterapia. O contexto fonético das amostras de fala influenciaram os julgamentos nas condições pré e pós-fonoterapia. Houve maior percentual de acerto para os juízes experientes condição pré-fonoterapia (p-valor <0,001).Conclusão: a experiência dos juízes e composição fonética das amostras de fala influenciam os julgamentos perceptivo-auditivos das AC.
Auditory-perceptual judgment of velar stops associated to cleft palate by judges with and without experience
Keywords: Cleft Palate; Speech; Speech Disorders; Auditory Perception; Fissura Palatina; Fala; Distúrbios de Fala; Percepção Auditiva